Synthesis, Optical and Electrical Properties of MXENE (Ti3C2Tx) Ink Fabrication for Coating Application - R. Jothi Ramalignam (22303663) (2025)
In this study, A colloidal solution of MXene containing multi and single-layered Ti3C2Tx was prepared by in-situ HF etching method from the precursor compound of Ti3AlC2. After ultrasonication, the as-prepared MXene ink appears from a green to a black solution. The as-prepared black powder of Ti3C2Tx in liquid and powder is further characterized by XRD, SEM, EDAX, and Electrical property characterization. We presented the detailed methodology for the MXene ink preparation and its electrical property characterization. As a result, we developed MXene ink obtained by the etching process in the measuring cloth. The homogeneity of the as-prepared ink is very efficient and shows promising conducting properties for future application study. Other Information Published in: Transactions on Electrical and Electronic Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42341-025-00587-y